Family functioning, hopelessnes and adolescents' depressive symptoms: moderating effects of gender, age and socio-economic status - Rodríguez-Naranjo, María Carmen; Caño-González, Antonio (My University, 2017)
Research has shown that difficulties in family functioning contribute to developing adolescents’ depressive symptoms. Since family functioning is primarily defined by broadband variables like cohesion or support, which represent family functioning as a whole, it is necessary to carry out a more fine-grained analysis of the family variables that are involved in the development of depressive symptoms at these ages. This study examined the relations between the family variables included in the MacMaster Model of Family Functioning (MMFF) and adolescents’ depressive symptoms, as well as the moderating effects of socio-demographic characteristics. Participants were 643 adolescents aged 12 to 18 years (49% male) drawn from secondary schools in Málaga (Spain). They completed the Family Assessment Device, which assesses the MMFF variables: problem solving, communication, roles, affective responsiveness, affective involvement and behavior control; the Beck Depression Inventory; the Beck Hopelessness Scale; and a socio-economic measure. The analytic strategy used was regression analysis, testing moderation and mediation effects. Results showed that both family functioning as a whole and each MMFF variable, as well as socio-economic status (SES), predicted adolescents’ depressive symptoms. In addition, gender moderated the relation of family behavior control and roles with depressive symptoms. Moreover, age moderated the relation between family affective involvement and depressive symptoms. Also, SES moderated the relation of family behavior control, roles, communication and affective responsiveness with depressive symptoms. Finally, both family functioning and SES contributed to hopelessness, which partially mediated the effect of family functioning on depressive symptoms, and totally mediated the effect of SES on depressive symptoms. These results point to the importance of identifying the family variables that are relevant for the design of interventions to prevent affective disturbances in adolescents with different socio-demographic characteristics. The effect of low family SES on adolescents’ depressive symptoms through the development of hopelessness should also be targeted.
Keywords: Depresión mental; Adolescentes -- Psicología; Depression; Adolescence